The Influence of Enxtrinsic Motivation and Competence on Innovative Behavior - Mahendra Wiratama; Hanif Aulawi (CAKRAWALA : Management Science Journal, 2024)
This study aims to test how and how much to test and analyze the effect of motivation on innovative behavior, to find out how much influence competence has on innovative behavior and to find out how much influence motivation and competence have on innovative behavior. The method used in this research is descriptive with a quantitative approach. Data collection techniques used in the study were observation and questionnaire collection. The population of this study were employees of the Industrial Human Resources Development Agency, the Apparatus Human Resources Education and Training division, and the Industrial Vocational Education Development Center with a total of 52 employees. The sample used was 52 employees of the Industrial Human Resources Development Agency of the Ministry of Industry of the Republic of Indonesia, the sample consisted of 25 employees from the Apparatus Human Resources Education and Training division, and 27 employees from the Industrial Vocational Education Development Center division. In this study, because the population was less than 100, the researchers used total sampling. Total sampling is a sampling method equal to the total population. The results of this study indicate that partially there is a positive and significant influence between extrinsic motivation variables on innovative behavior. This result is evidenced by the calculated t value of 3.913 with a significance value of 0.000 <0.05, and the coefficient value has a positive value of 0.427. The results of this study indicate that the competency variable partially has a significant influence on innovative behavior. This result is evidenced by the t test statistical test t value of 4.119 with a significant value of 0.000 <0.05 and the coefficient value has a positive value of 0.450. The results of the study simultaneously have a significant effect on Extrinsic Motivation and Competence on Innovative Behavior. This is evidenced by the calculated F statistic of 36.992 with a significance of 0.000. Because the significance value <0.05. The object of this research is the employees of Badan Pengembangan Sumber Daya Manusia (BPSDMI) (BPSDMI) Kementrian Perindustrian Republik Indonesia